2020
DOI: 10.1534/g3.119.400933
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Genetic Requirements for Zinc Tolerance and Toxicity inSaccharomyces cerevisiae

Abstract: Zinc is essential for almost all living organisms, since it serves as a crucial cofactor for transcription factors and enzymes. However, it is toxic to cell growth when present in excess. The present work aims to investigate the toxicity mechanisms induced by zinc stress in yeast cells. To this end, 108 yeast single-gene deletion mutants were identified sensitive to 6 mM ZnCl 2 through a genome-wide screen. These genes were predominantly related to the biological processes of vacuolar acidification and transpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 61 publications
1
22
0
1
Order By: Relevance
“…Some metal-containing compounds are also thought to act by inducing oxidative stress, and our data analysis showed that most of the metals in our survey (cadmium, copper, chromium, and aluminum) caused accumulation of reactive oxygen species. Zinc was not tested for ROS formation in a cell death context, but genome wide screening for resistance to zinc did show that numerous mutants formed ROS in its presence [163]. Only manganese stress did not cause ROS formation, though in one paper [164] its toxicity was dependent on the mitochondria, which might implicate ROS.…”
Section: Oxidantsmentioning
confidence: 99%
“…Some metal-containing compounds are also thought to act by inducing oxidative stress, and our data analysis showed that most of the metals in our survey (cadmium, copper, chromium, and aluminum) caused accumulation of reactive oxygen species. Zinc was not tested for ROS formation in a cell death context, but genome wide screening for resistance to zinc did show that numerous mutants formed ROS in its presence [163]. Only manganese stress did not cause ROS formation, though in one paper [164] its toxicity was dependent on the mitochondria, which might implicate ROS.…”
Section: Oxidantsmentioning
confidence: 99%
“…The first-strand cDNA synthesis was performed using the Primer Script RT reagent kit (Cwbiotech, China) according to the manufacturer's instructions. The expression mRNA levels of TRR1, TRX2, GSH1, SOD1, CTT1 and GPX2 were detected by quantitative PCR (qPCR) as described previously [57] (Additional file 1: Table S1). Each reaction was carried out in triplicate.…”
Section: Rna Extraction and Quantitative Pcr Analysismentioning
confidence: 99%
“…Therefore, the high concentration of iron in the medium may have increased the intracellular labile iron pool, which in turn generated ROS. Excess zinc can also cause an increase in ROS accumulation, and disrupt iron metabolism, such as Fe-S cluster synthesis, in S. cerevisiae [ 29 , 30 ]. Excess copper also generates ROS and causes oxidative stress, DNA damage, and membrane disruption in S. cerevisiae [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%